Self-reported oral health and quality of life in patients with type 2 diabetes mellitus in primary care: a multi-center cross-sectional study - Verhulst, Martijn JL (Diabetes Metab Syndr Obes, 2019)
Background: Guidelines for primary diabetes care recommend to pay attention to oral health in patients with diabetes mellitus type 2 (T2DM). However, research about dental care utilization and the extent of problems regarding oral health in these patients is limited. Purpose: To assess self-reported oral health, general health-related quality of life (QoL) and oral health-related QoL in patients with T2DM who regularly attend a family physician office. Methods: Family physician offices were recruited in the area of Amsterdam, the Netherlands, as part of a cluster-randomized controlled trial. At these offices, patients with T2DM were included by family physicians and/or nurse practitioners. Patient data on general characteristics, self-reported oral health (including periodontitis), general health-related QoL (SF-36) and oral health-related QoL (OHIP-NL14) were collected. Results: Twenty-four family physician offices participated, who enrolled 764 patients with T2DM (mean age: 65.9±10.7 years, 56% male, 16% smoker). Almost 11% of the patients were metabolically poorly controlled (HbA1c >63 mmol/mol), 39% were obese (body mass index≥30 kg/m(2)), 37% had hypertension (systolic blood pressure ≥140 mmHg) and 44% had dyslipidemia (LDL-cholesterol >2.5 mmol/L). About a quarter (24%) reported not to visit a dentist regularly and 30% did not have dental insurance coverage. Furthermore, 16% of the patients were edentulous and having full dental prostheses, while 29% had a partial dental prosthesis. Pain in the mouth, dry mouth and bad breath were reported by 15%, 37% and 12% of the patients, respectively. Almost 70% suffered from periodontitis. Oral health-related QoL was impaired in 19% of the patients, and those subjects also had worse general health-related QoL. Conclusion: Almost a quarter of patients with T2DM at Dutch family physician offices does not visit the dentist regularly. The estimated prevalence of periodontitis is particularly high, but other oral health complaints and impaired oral health-related QoL are also relatively common.